Is high-intensity interval training associated with higher dropout? - Reljic, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Regular exercise is known to prevent cardiovascular disease and a wide range of other health problems, yet a large proportion of adults in European countries are insufficiently active with 25-50% of individuals dropping out of an exercise program within the first six months [2]. Given that lack of time is the most common barrier to exercise, time-efficient exercise interventions are needed. High-intensity interval training (HIT) is a useful strategy and has been demonstrated to improve fitness and health parameters with substantially lower time effort compared with traditional continuous aerobic training. However, HIT may be inappropriate for sedentary individuals given its strenuous character [1,3]. Due to a lack of data on dropout in HIT-studies, this study assessed HIT-intervention trials with sedentary individuals that reported dropout. METHODS: Electronic databases (MEDLINE, PubMed, Google Scholar) were searched for research articles published from 2000-2015. Inclusion criteria were sedentary/untrained individuals or subjects with or without known cardiovascular disease/risk factors, aged >18 yrs, trial duration 3 weeks, information on dropouts/completers and a detailed description of the HIT-protocol. Dropout was defined as the proportion who completed the study. Associations were assessed by Spearman correlation coefficients. RESULTS: 52 studies (mean duration: 9.5±4.5 weeks) with 898 subjects (mean age: 43±17 yrs) were included in the analysis. Mean dropout rate was 9.3%. Dropout was associated with longer session time ( =0.36, P<0.05), exercise volume/week ( =0.33, P<0.05), total exercise volume/study ( =0.50, P<0.001) and study duration ( =0.45, P<0.001). Dropout was greater in studies using treadmill/running protocols (12.7%) compared to cycle-protocols (6.1%, P<0.05). Participant age and exercise intensity were not associated with dropout. CONCLUSION: Dropout in HIT appears to be lower compared to traditional exercise programs. Given the association between HIT-volume and dropout rate, future studies should identify the minimally effective dose of HIT needed to improve health status. Such efforts would be important to increase sustainability and public health impact.